Modos de aplicação e reaplicação de calcário nas culturas de milho e soja em plantio direto: Efeito residual - Oliveira, Wandemberg Assis Silva [UNESP] (2013)
Studies involving liming and tillage are still needed to further recommendations of this practice in many different soils and climatic conditions where this system is used for cultivation. In this context, this study was conducted at experimental area UNESP - Ilha Solteira Campus, located in Selvíria county, Mato Grosso do Sul State, Brazil, with the objective to evaluate the effect of doses, methods of application and reapplication of limestone in corn and soybean crops in no-tillage system. In crop year 1999/00, began an experiment with modes of limestone application and cover crops, using the completely randomized design with treatments arranged in a factorial 4 x 2, or 4 modes of limestone application (incorporated, surface, surface before cover crop management and without liming ), 2 cover crops (millet and oats) before corn or soybeans crops. In treatments where there was limestone application, the dose used was 1,235 kg ha -1 with PRNT 91%. During the growing season 2002/03, wasn't longer considered as cover crops treatment and a new dose (769 kg ha -1 ) surface was reapplied in the presence or absence of scarification. In the treatment with limestone application on surface before cover crops management, it was applied 0.5, 1.0, 1.5, 2.0 and 2.5 times respectively the calculated dose for the other treatments. In the years 2003/04 and 2004/05 was evaluated the residual effect of the treatments. In crop year 2005/06, were kept modes of application of limestone, used in the experiment, and there was reapplication of two different types of limestone (C1 - PRNT 91% and C2 - PRNT 81.9%) in doses of 841.2 and 900.6 kg ha -1 respectively and on treatment CM doses limestone C1 were compared again. In 2006/07 and 2007/08, remained the treatments used in the previous year, thus attempting to evaluate the residual effect of the treatments. In 2008/ 09, before the sowing of corn and soybeans, was reapplied a new dose of limestone with ...